PENGARUH STRUKTUR AKTIVA DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PT. ASURANSI RELIANCE INDONESIA - Rahmat Hidayat Harahap; Vienlly Wietono; Edison Sagala; Elidawati (JURNAL BISNIS KOLEGA, 2019)
Abstract. Capital structure is related to the amount of long-term debt in the form of a term loan and own capital used to finance the company's assets. Capital structure is also very important for the company because it involves the policy of using the most profitable sources of funds and is part of the financial structure as a permanent expenditure that reflects the comparison between long-term debt with own capital seen from the asset side that reflects the wealth structure in a company. Companies that have high profits will have large internal funding capabilities and can optimize their financial management. By looking at the benefits of a company, it can be determined that the company includes a large company or a small company. The purpose of this study is to test and analyze how the influence of asset structure and profitability on the capital structure at PT. Asuransi Reliance Indonesia Medan branch 2015-2017.The research method used in this study is a quantitative method approach. In this study the data used are primary and secondary data. The data analysis technique used is multiple linear regression. This analysis uses a sample of 31 data. Results based on simultaneous analysis of asset structure and profitability do not affect the capital structure at PT. Insurance Reliance Indonesia. Partially, the asset structure variable to the capital structure has no effect and there is a variable profitability that does not affect the capital structure at PT. Insurance Reliance Indonesia.                            Keywords: Asset Structure, Profitability, Capital Structure.